Intersubjectivity and interlocution in causalrelations: The functionality of causalconjunctions in Portuguese - De Moura Neves, Maria Helena [UNESP] (My University, 2014)
This study approaches the expression of causality in the clause combining in Portuguese, considering, as fundamental, the thread that exists between the performance, in the socio-interaction, and cognitive trigger, based on intersubjectivity. Given that grammar is responsible for the functional organization of those relationships, the study examines the conjunctions traditionally considered as causal, especially those constructs invested with effects that go beyond the strict direction cause-consequence. After evaluating the proposal of formation of causal conjunction blocks with similar behavior, in contrast with others, we arrive at the discussion of the functional uniqueness of the conjunction porque (because).
Intersubjetividadeeinterlocuçãonas relações decausalidade. a funcionalidadedos juntivos causais na língua portuguesa
Keywords: Causal conjunctions; Causality in grammar; Interlocution and intersubjectivity